A New Outbreak in Sea Bass Farming in Turkey: Aeromonas veronii - TANSEL TANRIKUL, T; DINÇTÜRK, E (Journal of the Hellenic Veterinary Medical Society, 2021)
Turkey produces most of the European sea bassin Europe and bacterial diseases are the main cause of economic loss during the production cycle. This research presents the first extended study of the Aeromonas veronii infection in sea bass on the Turkish coast of the Aegean Sea. An outbreak was observed in three different sea bass farms and diseased fish with clinical symptoms were sampled. Abdominal distention, hemorrhages on the body and anus, enlarged spleen and liver, and hemorrhages in the internal organs were detected from clinical and pathological examinations. Biochemical and molecular identification confirmed the pathogen to be A.veronii.The histopathological observations demonstrated that the pathogen caused bacterial colonies in the fibrous connective tissue, granuloma, and vacuolar degeneration.The primary causes of the disease were proved through an infection experiment. 80% and 90% mortality were calculated in 0.85 x 108 CFU ml-1 and 1.28 x 108 CFU ml-1 experimentally infected groups with clinical and pathological signs of the disease respectively. Recently, the pathological symptoms of the disease had been confused with pasteurellosis infection in cage farms but the presence of A.veronii has been confirmed in the current study. A detailed study is needed to investigate the overall status of the disease in the Aegean Sea in order to design an appropriate preventive strategy.